2010
DOI: 10.1007/s10823-010-9123-9
|View full text |Cite
|
Sign up to set email alerts
|

Views of First Nation Elders on Memory Loss and Memory Care in Later Life

Abstract: Little is known about Indigenous communities and dementia and Elders have not been involved as advisors or participants in most research to date. This exploratory research sought to address this gap through a constructivist grounded theory project on the views of First Nation Elders on memory loss and memory care in later life, conducted in collaboration with decision-makers from the local Health Authority and Elders from three First Nation communities in British Columbia, Canada. Elders served as advisors to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
108
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(108 citation statements)
references
References 40 publications
0
108
0
Order By: Relevance
“…The findings from the Perceptions Project and the literature review found that Indigenous cultural and Western understandings of dementia differ. Most Indigenous people accept memory loss and confusion as a normal part of the aging process and these understandings are intimately connected to Indigenous values and worldviews (Hulko et al 2010;Jacklin et al 2014aJacklin et al , 2014bJacklin et al , 2014cJacklin et al 2013b;Jacklin et al 2013c;Lanting et al 2011;Pace et al 2013). In the environmental scan, the authors found that many of the resources developed by Alzheimer's organizations described dementia as an irreversible disease affecting the brain, causing deterioration of memory and the ability to think; and is also described as causing behavior and emotional changes that interfere with the person's social and work life (Alzheimer Society of Canada 2010).…”
Section: Fact Sheet 1: What Is Dementia? First Nations Perspectives Amentioning
confidence: 99%
See 3 more Smart Citations
“…The findings from the Perceptions Project and the literature review found that Indigenous cultural and Western understandings of dementia differ. Most Indigenous people accept memory loss and confusion as a normal part of the aging process and these understandings are intimately connected to Indigenous values and worldviews (Hulko et al 2010;Jacklin et al 2014aJacklin et al , 2014bJacklin et al , 2014cJacklin et al 2013b;Jacklin et al 2013c;Lanting et al 2011;Pace et al 2013). In the environmental scan, the authors found that many of the resources developed by Alzheimer's organizations described dementia as an irreversible disease affecting the brain, causing deterioration of memory and the ability to think; and is also described as causing behavior and emotional changes that interfere with the person's social and work life (Alzheimer Society of Canada 2010).…”
Section: Fact Sheet 1: What Is Dementia? First Nations Perspectives Amentioning
confidence: 99%
“…The results suggested that the term dementia may or may not be an accepted or conceptually understood term for all Indigenous people (Hulko et al 2010;Sutherland 2007), and that there may be some underlying shame or stigma associated with the disease (Pace et al 2013). Furthermore, there is an absence of the word "dementia" in Indigenous languages.…”
Section: Fact Sheet 1: What Is Dementia? First Nations Perspectives Amentioning
confidence: 99%
See 2 more Smart Citations
“…Todd Cappo, the community health program coordinator at FHQTC Health Services, explained this role as: "One that understand[s] our ceremonies, the value of our culture, and our medicines." Knowledge Keepers provide a link between the past and present, creating a sense of cultural continuity despite ever-changing community health needs and responses (Hulko et al, 2010).…”
Section: Researching Dementia In the File Hills Qu'appelle Tribal Coumentioning
confidence: 99%